Принципи підбору пар для гібридизації в селекції озимої пшениці T. aestivum L. на адаптивність до умов довкілля - Бурденюк-Тарасевич, Л.А.; Лозінський, М.В. (Фактори експериментальної еволюції організмів, 2015)
Aims. The study assess different approaches to evaluation of the source material and breeding pairs selection for Triticum aestivum L. winter on adaptability for agroecological zone of Ukraine’s forest steppe conditions. Methods. Different ecotype varieties and hybrid population lines became sources for breeding. Field, laboratory, statistical and visual methods used in offi cial state evaluation were used for characterization of the useful traits. Results. In genealogy of Bila Tserkva varieties one parent is original intensive type variety or the best subpopulation defi ned in competitive quality testing, created and adapted to the conditions of forest-steppe of Ukraine. The second parent is geographically and genetically distant or variety originated from the steppe, Western European, North Caucasus, or Volga ecotypes. Conclusions. Interspecies invariant hybridization was found to be an effi cient method of assessment.To enforce selected traits of the variety backcross with one the parentsis used. Stable Chernobyl radiomutants resistance to biotic and abiotic stress factors and increased protein contents were used to enrich germplazm. Keywords: wheat, breeding, adaptability, varieties, crossing.